Local control and survival after stereotactic body radiation therapy of early-stage lung cancer patients in Slovenia - Stanič, Karmen (Radiology and oncology (Ljubljana), 2023)
Background. Stereotactic body radiation therapy (SBRT) precisely and non-invasively delivers ablative radiationdose to tumors in early-stage lung cancer patients who are not candidates for surgery or refuse it. The aim of researchwas to evaluate local control, overall survival (OS), local progression free survival (LPFS), distant metastases free survival(DMFS), disease free survival (DFS) and toxicity in early-stage lung cancer patients treated with SBRT in a single tertiarycancer centre.Patients and methods. We retrospectively evaluated medical records and radiation treatment plan parametersof 228 tumors irradiated in 206 early-stage lung cancer patients between 2016 and 2021 at the Institute of OncologyLjubljana.Results. After 25 months of median follow up, 68 of 206 (33%) patients died. Median OS was 46 months (CI 36 -56),1-year, 2-year and 3-year OS were 87%, 74% and 62% and 5-year OS was 31%. A total of 45 disease progressions havebeen identified in 41 patients. Local progress only was noticed in 5 (2%) patients, systemic progress in 32 (16%) andcombined systemic and local in 4 (2%) patients. Local control rate (LCR) at 1 year was 98%, at 2 and 3 years 96%and 95% at 5 years. The 1-, 2- and 3-year LPFS were 98%, 96% and 94%, respectively and 5-year LPFS was 82%. One,2-, 3- and 5-year DFS w ere 89%, 81%, 72% and 49%, respectively. Among 28 toxicities recorded only one was Grade4 (pneumonitis), all others were Grade 1 or 2. No differences in LCR, LPFS, DFS were found in univariate analysis com-paring patient, tumor, and treatment characteristics. For OS the only statistically significant difference was found inpatients with more than 3 comorbidities compared to those with less comorbidities.Conclusions. Early lung cancer treated with SBRT at single tertiary cancer centre showed that LCR, LPFS, DFS, DMFSand OS were comparable to published studies. Patients with many comorbidities had significantly worse overallsurvival compared to those with less comorbidities. No other significant differences by patient, tumor, or treatmentcharacteristics were found for DMFS, LPFS, and DFS. Toxicity data confirmed that treatment was well tolerated.
Keywords: early-stage lung cancer; lung cancer; rak pljuč; stereotactic body radiotherapy; stereotaktična radioterapija; zgodnji stadij pljučnega raka